Appraisal on Special Ayurvedic Dietary Formulas for Metabolic Syndrome (International Journal of Ayurveda and Pharma Research, 2021)
Metabolic syndrome and related complications are a major challenge for health providers of present era. Metabolic syndrome with key characters of abdominal obesity, insulin resistance, hypertension and dyslipidemia are the outcomes of faulty diet and habits. Since there are no such pharmacological agents which can reverse this condition more importance is being given to diet and lifestyle modifications. Traditional medicinal systems like Ayurveda gives equal importance for food and nutrition in both health and diseased conditions. Concept of Pathya -apathya for each and every disease is unique to Ayurveda where the macro and micronutrient principles were selected rationally for each disease conditions. These very principles can be adopted along with dietary supplements for curbing modern lifestyle disorders, more over there is mentioning of similar conditions in classics under a board term of Santharpanajanya Vikaras. Materials and methods- Thorough literary search done on various classical Ayurvedic texts for various diet and dietary preparations and online bases for their pharmacological properties from Ayurvedic and modern perspective and enlisted the dietary supplements. Results- Selected three major ingredients for the macro nutrient principles carbohydrate, protein and fat suggestive for MS from Sthoulya Prakarana and their properties are critically reviewed. Conclusion- There is enough scope of research in Ayurvedic dietary supplements for obesity and Metabolic Syndrome.